Efeitos dinâmicos em estruturas devidos à turbulência atmosférica - Pedro Vianna Pessoa de Mendonca (1991)
The main purpuse of this work is to disseminate the knowledge necessary to understand and apply a process to compute the static equivalent loads that substitute the dynamic effects caused by the atmospheric turbulence over the structures, according to the Chapter 9 of the Brazilian Code NBR 6123, concerning wind loads.This method transforms the dynamic nondeterministic wind loads into static deterministic equivalent loads along the height of the structure.A microcomputer program implementing this method is presented to permit the user to find the static equivalent loads. These loads can be used as input to a program of structural analysis.